Lessons learned from ECMO support in pediatric patients with D-transposition of the great arteries: preoperative, intraoperative and postoperative. Issue 4 (28th September 2021) - Yang, Lijun; Ye, Lifen; Yu, Jiangen; Li, Jianhua; Zhang, Zewei; Shu, Qiang; Lin, Ru
Abstract : Background: Extracorporeal membrane oxygenation (ECMO) support on D-transposition of the great arteries (D-TGA) carries formidable challenges. Methods: A retrospective study was performed on pediatric patients with D-TGA supported by ECMO from July 2007 to December 2019. This study summarized the clinical experience of ECMO support in pediatric patients with D-TGA preoperative, intraoperative, and postoperative. Results: Overall, 16 children with D-TGA received ECMO support during this period. Two (2 of 16) were supported before cardiac surgery, 3 (3 of 16) were supported postoperatively in the intensive care unit, and 11 (11 of 16) failed to wean off cardiopulmonary bypass. Two cases of preoperative ECMO support for patients with D-TGA with an intact ventricular septum and restrictive atrial septum due to severe hypoxemia died. In this study, D-TGA with coronary artery malformation and other complicated deformities died (8 of 14), whereas uncomplicated D-TGA without coronary artery malformation all survived (6 of 14). The wean-off rate of ECMO patients supported in D-TGA was 62.5% (10 of 16), while the 30-day survival rate was 44% (7 of 16). Conclusion: Although a promising ECMO weaning rate was obtained, 30-day survival of this population was frustrating, mainly attributed to the original anatomy of coronary arteries and the concomitant deformities.